Sclerosing Ovarian Tumor with Disrupted Morphology: Significance of Ancillary Tests in Resolving Diagnostic Dilemma - Rao, Shalinee; Muralitharan, Susruthan; Narayanan, Cunnigaiper Dhanasekharan (Indian Journal of Medical and Paediatric Oncology, 2018)
Sclerosing stromal tumor is an uncommon subtype of sex cord–stromal tumor of the ovary. It occurs in young females who present with pelvic pain and menstrual irregularities. We present a case of an 18-year-old female who was brought to emergency room with a history of blunt trauma abdomen after road traffic accident. A diagnosis of hemoperitoneum was made, and the patient underwent emergency exploratory laparotomy. An incidental right ovarian mass was found which was removed and sent for histopathological examination. Histomorphology of this lesion showed variable findings with extensive edema and paucicellularity. Few thin wall blood vessels were also observed. The possible differential diagnosis on gross and microscopic examination included sclerosing stromal tumor, fibroma, thecomas, granulosa cell tumor, and edema of the ovary. In view of diagnostic dilemma, special stains for collagen and reticulin were done. In addition, immunohistochemistry (IHC) for CD99, smooth muscle actin, and desmin was put up. A diagnosis of sclerosing tumor of the ovary was made based on histomorphology and findings of ancillary tests. In general, ancillary tests are not required to diagnose sclerosing ovarian tumor as it has characteristic histological features. This case highlights the usefulness of special stains and IHC in sex cord tumors with overlapping microscopic features.
Keywords: Atypical; histomorphology; immunohistochemistry; reticulin stain; sclerosing stromal tumor